STRUKTUR STOMATA DAUN BEBERAPA TUMBUHAN KANTONG SEMAR (Nepenthes spp.) - Lince Meriko (Research Center for Biology-Indonesian Institute of Sciences, 2017)
The exploitation of pitcher plants (Nepenthes spp.) for economics interest and forest degradation make a higher extinction risk for Nepenthes globally. This research was aimed to examine anatomical structure of stomata of Nepenthes gracilis, N. reinwardtiana, N. ampullaria. The result showed that the type of stomata of N. gracilis and N. reinwardtiana has the actinocitic type while, N. ampullaria has anomocitic stomata type.